2011
DOI: 10.4028/www.scientific.net/amr.175-176.143
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ultrasonication on the Gelation Velocity and Structure of Silk Fibroin

Abstract: Silk fibroin hydrogels is an important morphous of biomaterial. As a natural protein collosol, purified native silk fibroin solution can be gelatinized under certain conditions. The main mechanism of the gelation is that the fibroin molecules turn into the β-sheet conformation from the random coils. This transformation of silk fibroin molecules would be influenced by various parameters such as the temperature, pH value, ion concentration and so on. In this paper, the effect of ultrasonication on the gelation v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“… [40] also confirmed that the conformation of silk fibroin would undergo transformation with the increase of ultrasonic power. Besides, some studies [41] , [42] , [43] also proved that the long-time sonication could make the random coils converted to stable β -sheet structures and accelerate the formation of silk fibroin gels. Therefore, ultrasound time and power can precisely regulate the secondary structures and the crystallinities of silk fibroin materials.…”
Section: Resultsmentioning
confidence: 99%
“… [40] also confirmed that the conformation of silk fibroin would undergo transformation with the increase of ultrasonic power. Besides, some studies [41] , [42] , [43] also proved that the long-time sonication could make the random coils converted to stable β -sheet structures and accelerate the formation of silk fibroin gels. Therefore, ultrasound time and power can precisely regulate the secondary structures and the crystallinities of silk fibroin materials.…”
Section: Resultsmentioning
confidence: 99%
“…Silk fibroin , has an amino acid sequence consisting of repeats of glycine-alanine-glycine-alanine-glycine-serine (GAGAGS) that self-assemble to form beta sheets. Formation of beta sheets may be triggered by various processing techniques that involve energy input (e.g., sonication or vortexing), lowering the solution pH, or through dehydration of the protein by removal of water (e.g., by methanol treatment). Beta sheets are highly crystalline and serve to physically cross-link the protein through intra- and intermolecular hydrogen bonding and van der Waals interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The decrease of Δ C p suggests that the β -sheet crystalline content of the system increases with increasing sonication time. Other studies [13] , [14] , [36] , [8] have also determined that long-term ultrasonic treatment can transform the random coil protein structure into a stable β -sheet structure. These findings are consistent with our findings that ultrasonic time influences the transformation of the secondary structures in SPI/SF materials.…”
Section: Resultsmentioning
confidence: 98%
“…Silk fibroin protein chains exist as aggregates and micelles in the silkworm's glandular, forming a β -sheet structure when the silkworm spits out, with a crystallinity of about 75% [12] , [13] . Previous studies [1] , [2] , [14] , [15] , [16] found that the molecular chain of silk fibroin consist of an H-chain and an L-chain as well as a P25 protein. This factor plays a crucial role in the thermal and mechanical properties of silk.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation